2021
DOI: 10.3389/fmicb.2021.642959
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals a Dependent Relationship Between Rumen Bacteria and Diet of Grass- and Grain-Fed Yaks

Abstract: Current information on the differences between rumen bacteria and metabolites of the grass-fed and grain-fed yaks is limited. Understanding the composition and alterations of rumen microbial metabolites is important to clarify its potential role in grass-fed and grain-fed systems. The aim of this research was to explore the influence of different production systems on the functional attributes and metabolites in the rumen microbiota of yak using genomics (Illumina MiSeq sequencing of the 16S rRNA gene) and unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
6
14
1
Order By: Relevance
“…This may be because there is much less crude fiber in grain than in forage. Similar results were reported by Xu et al (11) in a study exploring the differences in rumen bacteria between grass-fed and grain-fed yaks. A comprehensive analysis of the composition of the yak rumen microbiota would provide important insights into microbially mediated metabolic processes.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may be because there is much less crude fiber in grain than in forage. Similar results were reported by Xu et al (11) in a study exploring the differences in rumen bacteria between grass-fed and grain-fed yaks. A comprehensive analysis of the composition of the yak rumen microbiota would provide important insights into microbially mediated metabolic processes.…”
Section: Introductionsupporting
confidence: 90%
“…There is increasing evidence that animal phenotypic characteristics are closely related to rumen microbes, and that the concentrations of metabolites in the rumen affect rumen bacterial function ( 10 , 11 , 63 ). Overall, the relative changes of rumen microbes and metabolites and their associations may be the main factors affecting yak production performance.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that LA and SA systems differ not only in the relative abundance of species but also in the taxonomic composition with distinctive species in both systems. At the phylum level, Bacteroidetes and Firmicutes were the two most abundant classifications in both systems, which agrees with the previous ruminant studies (Xu et al, 2021 ; Zhang et al, 2021 ). Bacteroidetes as one of the most abundant phyla in the rumen has a wide range of sugar degradation and protein hydrolysis potential, which is significant for the digestion and utilization of non-fibrous polysaccharides and proteins (Woodmansey, 2007 ; De Mulder et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Diet is one of the important factors affecting rumen microbial diversity, due to microbial preferences for specific substrates. Previous studies have shown that high forage diet significantly increased the relative abundance of fibrobacterota (Pandit et al, 2018 ; Xu et al, 2021 ). Forages with different nutritional quality can also affect rumen microorganisms.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies indicate that the species diversity and abundance of rumen microorganisms play a critical role in maintaining host physiology (Xu et al, 2021). While Chao1 and ACE indices are primarily used to measure species richness, the Simpson and Shannon indices combine the richness and evenness of a species.…”
Section: Discussionmentioning
confidence: 99%